DAMPAK PERUBAHAN GUNA LAHAN TERHADAP KEMAMPUAN RESAPAN AIR (KASUS: KOTA SAMARINDA) - Warsilan, Warsilan (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2019)
As the capital of the province of East Kalimantan, Samarinda City developments has a rapid progress from year to year. Samarinda City Development has a tendency oriented towards infrastructure development without regard to the existence of the quality of the existing environment. Imbalance of development in Samarinda city is to start decreasing the water catchment area, so its make increasing intensity of flood in the Samarinda City. The purpose of this study was to analyze the impact of changes in land use in the Samarinda city on the ability of the water catchment area. This research method using descriptive approach, the data collection system of primary and secondary. Intensity flood in the Samarinda city  is increasing from year to year, this condition happened as a problem that always occurs during the rainy season. Current development trends, always take an area that should be an infiltration  area for Samarinda City. Culture and inadequate infrastructure conditions such as lack of system of drainage and polder, was another factor causing the high intensity of flood  in Samarinda City. Therefore, the relevant regulations development guidelines for Samarinda  City must consider all aspects of planning, in this case especially the important of a balance of cultivated land and protected areas or zones.Keywords: Changes in land use; intensity of puddles; Samarinda